The Role of Product Innovation and Market Orientation in Achieving Competitive Advantage in Cashew Guava UMKM in Central Buton Regency - Andry Stepahnie Titing; Muhamad Stiadi; Elin Meiliasasmita. R (Universitas Bumigora, 2023)
This study aims to determine: (1) The Role of Product Innovation in achieving Competitive Advantage in Cashew MSMEs in Central Buton Regency. (2) The role of Market Orientation in achieving Competitive Advantage in Cashew MSMEs in Central Buton Regency. This research uses an approach with Quantitative methods, Data collection in this study used Literature Study and Questionnaire Distribution. The population of this study were all cashew MSME business actors in Central Buton Regency. While the sample of this study amounted to 48 people. Testing this research instrument using the Validity Test and Reliability Test with SPSS 25.0. The data analysis technique used in this study is the measurement model test (outer model) and structural model testing (inner model) with Smart PLS 3.0. Based on the results of the study, it is known that there is a positive and significant influence between the Product Innovation variable on Competitive Advantage as indicated by the t-statistic value of 2.180 with a P-Value of 0.030 and the Market Orientation variable also has a positive and significant effect on Competitive Advantage as indicated by the t-statistic value of 5.143 with a P-Value of 0.000.